Stereotactic body radiotherapy to treat small lung lesions clinically diagnosed as primary lung cancer by radiological examination: A prospective observational study. (August 2018) - Inoue, Tetsuya; Katoh, Norio; Ito, Yoichi M; Kimura, Tomoki; Nagata, Yasushi; Kuriyama, Kengo; Onishi, Hiroshi; Yoshitake, Tadamasa; Shioyama, Yoshiyuki; Iizuka, Yusuke; Inaba, Koji; Konishi, Koji; et al.
Highlights: Small lung lesions were clinically diagnosed as primary lung cancer. Stereotactic body radiotherapy was performed in prospective multi-institutional study. Stereotactic body radiotherapy is reasonably safe and effective. Abstract: Objectives: Even with advanced image guidance, biopsies occasionally fail to diagnose small lung lesions, which are highly suggestive of primary lung cancer by radiological examination. The aim of this study was to evaluate the outcome of stereotactic body radiotherapy (SBRT) to treat small lung lesions clinically diagnosed as primary lung cancer. Materials and methods: This is a prospective, multi-institutional observation study. Strict inclusion and exclusion criteria were determined in a nation-wide consensus meeting and used to include patients who were clinically diagnosed with primary lung cancer using precise imaging modalities, for whom further surgical intervention was not feasible, who refused watchful waiting, and who were highly tolerable of SBRT with informed consent. SBRT was performed with 48 Gy in 4 fractions at the tumor isocenter. Results: From August 2009 to August 2014, 62 patients from 11 institutions were enrolled. Their median age was 80 years. The tumors ranged in size from 9 to 30 mm in diameter (median, 18 mm). The median follow-up interval was 55 months. The 3-year overall survival rate was 83.3% (95% confidence interval (CI) 71.1–90.7%) for all the patients and 94.7% (95% CI 68.1–99.2%) for the patients younger than 75 years. Local failure, regional lymph node metastases and distant metastases occurred in 4 (6.4%), 3 (4.8%) and 11 (17.7%) patients, respectively. Grades 3 and 4 toxicities were observed in 8 (12.9%) patients and 1 (1.6%) patient, respectively. No grade 5 toxicities were observed. Conclusions: SBRT is safe and effective for patients with small lung lesions clinically diagnosed as primary lung cancer that satisfied the proposed strict indication criteria as previously reported. A prospective interventional study is required to ascertain if SBRT is an alternative strategy for these patients.